ANALYSIS OF FACTORS INFLUENCING ACCOUNTING STUDENTS’ INTEREST IN CHOOSING A CAREER AS AN AUDITOR AT UNIVERSITAS SAINS INDONESIA - Sesilia, Lia; Hardianto, Ade Manggala; Maulana, M. Afrizal; Novitasari, Yuli (International Journal of Multidisciplinary Research and Literature, 2026)
This study aims to analyze the factors influencing accounting students' interest in pursuing a career as auditors at Universitas Sains Indonesia. A quantitative approach was applied using multiple linear regression analysis. The results indicate that Work Environment, Financial Rewards, and Professional Training each have no significant effect on students' career interest. In contrast, Job Market Considerations show a positive and significant effect, supported by a significance value of 0.010. Simultaneously, all independent variables significantly influence students' interest, as indicated by the F-test (p = 0.009). These findings highlight that job market prospects are the primary factor shaping students' decisions to select auditing as a career path.